2021
DOI: 10.3390/jcs5080204
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Shielding Effectiveness of Glass Fiber/Epoxy Laminated Composites with Multi-Scale Reinforcements

Abstract: In this study, an experimental investigation has been performed to understand the electromagnetic interference-shielding effectiveness (EMI-SE) of glass fiber/epoxy laminated composites embedded with carbon nanotubes (CNTs) and Fe3O4 nanoparticles, reinforced with micro carbon fibers along the thickness direction. Micro carbon fibers were reinforced along the thickness direction between the laminates using an electro-flocking process and a vacuum infusion process used to fabricate the composites. The EMI-SE of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The electrical conductivity of the FCM containing 20 wt.% NCGF reached 6.68 x 10 -6 S/m, while the electromagnetic shielding properties exceeded 20 dB. Yesmin & Chalivendra [18] investigated the effect of CNT, micro-carbon fibers, and Fe 3 O 4 nanoparticles, deposited by paintbrushing on GF fabric, on electromagnetic shielding effectiveness of epoxy-matrix composites in the X-band frequency range and found that the nanoparticles had a major influence on the total shielding effectiveness as well as on the absorption. Airbrushing could thus be an efficient method for CNT deposition on GF to achieve a thin layer with high CNT concentration, since it is an easily controllable process and requires few devices to perform the deposition.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The electrical conductivity of the FCM containing 20 wt.% NCGF reached 6.68 x 10 -6 S/m, while the electromagnetic shielding properties exceeded 20 dB. Yesmin & Chalivendra [18] investigated the effect of CNT, micro-carbon fibers, and Fe 3 O 4 nanoparticles, deposited by paintbrushing on GF fabric, on electromagnetic shielding effectiveness of epoxy-matrix composites in the X-band frequency range and found that the nanoparticles had a major influence on the total shielding effectiveness as well as on the absorption. Airbrushing could thus be an efficient method for CNT deposition on GF to achieve a thin layer with high CNT concentration, since it is an easily controllable process and requires few devices to perform the deposition.…”
Section: Introductionmentioning
confidence: 94%
“…Decreasing the size of CNT clusters, the EMI SE of silicon rubber/CNT composites enhanced, due to the increase of interfacial contact area [10] . The use of CNT in nanocomposites with epoxy, other resins and glass fibers (GF) for EMI shielding has been reported by several authors [5,[11][12][13][14][15][16][17][18][19][20][21] . In one of the first works on this type of EMI material, Park et al [5] reported that epoxy resin/GF composites containing up to 5 wt% CNT have reached 20 dB (99% of effectiveness) in 300 MHz -1 GHz, with the highest value of electrical permittivity obtained for composites with 3% and 5 wt% CNT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon fibers of three various lengths (80, 150, and 350 mm), two different fiber densities (1000 and 2000 fibers/mm 2 ), along with two different quantities of Fe 3 O 4 nanoparticles were used to study the effect (0.5 and 1 wt%) on EM properties. Composite with micro carbon fibers of 350 mm length and a density of 2000 fibers/mm 2 with 1 wt.% of Fe 3 O 4 nanoparticles had the highest total SE value [75].…”
Section: Effect Of Iron Based Additives On Microwave Absorptionmentioning
confidence: 99%
“…Here, the fibers assume the primary load-bearing role, while the matrix serves as both a load transfer medium and a protective barrier against harsh environmental conditions. [11][12][13][14][15][16][17] Epoxy, among thermosetting polymers, holds particular significance due to its outstanding mechanical properties, cost-effectiveness, ease of fabrication, thermal stability, and resistance to chemical degradation. Consequently, it finds application in diverse industries, including automotive, construction, aerospace, energy storage, petrochemicals, and composites.…”
Section: Introductionmentioning
confidence: 99%